2005
DOI: 10.1128/aac.49.12.5162-5165.2005
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the In Vitro Effectiveness of Antimicrobials against Mycoplasma mycoides subsp. mycoides Small-Colony Type To Reduce Contagious Bovine Pleuropneumonia Infection

Abstract: In vitro minimum inhibitory concentrations were determined for 21 antimicrobials against 41 isolates of Mycoplasma mycoides subsp. mycoides small-colony type, the cause of contagious bovine pleuropneumonia. Of the antimicrobials used most widely in Africa, oxytetracycline and tilmicosin were effective, while the isolates were resistant to tylosin. These results provide a baseline for monitoring antimicrobial resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 5 publications
3
13
0
1
Order By: Relevance
“…Moreover, their MIC 50 and MIC 90 values showed that these antimicrobials are not effective against this pathogen. These results are in agreement with those described in previous studies performed on other mycoplasma species [8, 10, 11, 33]. Hence, our work supports the previously proposed hypothesis about an intrinsic resistance of the mycoplasmas of the M .…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, their MIC 50 and MIC 90 values showed that these antimicrobials are not effective against this pathogen. These results are in agreement with those described in previous studies performed on other mycoplasma species [8, 10, 11, 33]. Hence, our work supports the previously proposed hypothesis about an intrinsic resistance of the mycoplasmas of the M .…”
Section: Discussionsupporting
confidence: 94%
“…A number of products have demonstrated efficacy against MmmSC in vitro, including oxytetracycline (OTC), danofloxacin and tilmicosin (Ayling et al, 2000(Ayling et al, , 2005. Modelling studies have predicted that antimicrobials, used in association with vaccination, could be successful in eradicating disease from infected herds (Mariner et al, 2006b).…”
Section: Introductionmentioning
confidence: 99%
“…The increasing use of antibiotics by herdsmen despite the risk of creating a carrier state in an animal is probably an attempt to alleviate the suffering of the affected cattle as reported by Mariner et al (2006). However, , Yaya et al (2004) and Ayling et al (2005) stated some beneficial effects on the use of antibiotics in the treatment of CBPP amongst which include limiting the clinical severity of the disease. But however, complete elimination of the causative organism from the affected cattle may not be achieved, thereby creating a potential pool of disease carrier.…”
Section: Resultsmentioning
confidence: 99%